A Microscopic Analysis of Crowd Behaviour at Dewan Sultan Ibrahim (DSI), UTHM on Convocation Day during the Emergency Situation by using the Crowd Behavior Simulator for Disaster Evacuation (CBS-DE) Method - Abustan, Muhammad Salleh; Mohamad Ali, Mohd Firdaus; Abu Talib, Siti Hidayah; Adnan, Mohd Shalahuddin (International Journal of Integrated Engineering, 2018)
This research focuses on the demonstration of the evacuation simulation as if emergency situation is occurred at Dewan Sultan Ibrahim (DSI) of Universiti Tun Hussein Onn Malaysia (UTHM) from the perspective of microscopic dynamics of crowd behaviour. The model was performed by using the DEM-based crowd behaviour simulator, namely as Crowd Behavior Simulator for Disaster Evacuation (CBS-DE) and its analysis is capable to track the trajectory and rotation of each individual. This research is based on two different cases in which the first case was using the average velocity of 1.16 m/s for both male and female and the for the second case, the velocity of 1.25 m/s was applied for male while lower velocity was applied for female which is 1.12 m/s. DSI building is considered as a well-designed building in terms of safety and convenience factors. This is due to the short time taken for the people to evacuate from the inside of the building by considering the crowds are familiar with the building as all the doors are easy to be seen.